Convergence Processes in Regional Online Media (Based on Online Resources of the Mari El Republic) - S.Yu. Smirnova; E.V. Karpova (Ученые записки Казанского университета: Серия Гуманитарные науки)
Online media of the Mari El Republic were studied by the authors of this paper for the use of multimedia technologies in order to find out how convergence processes take place in the regional online media. Journalists are losing their previous specific qualification, thereby becoming multimedia experts. However, is this true for regional online media? The study involves the content analysis of four online resources, analysis of the editorial assignment for correspondents, and monitoring of publications on websites of the regional media. The following media were analyzed: “MediaPotok” news agency, as well as websites of such newspapers as “Krasnyi Gorod”, “Yoshkar-Ola”, and “Mariiskaya Pravda”. The results of the content analysis were presented in the table as a percentage. The authors concluded that regional online media are currently not using multimedia tools in full, being content with a narrow set of technologies they have already mastered. The convergence process proceeds quite slowly. The websites have no infographics, podcasts, gif animation, and “coubs”. External links and polls are barely used. Regional online-media basically use photos and videos in their materials. Furthermore, journalists’ blogs and user-generated content are popular. The results of the study can help the online media of the Mari El Republic to start applying new technologies in preparation of the content.